2019
DOI: 10.5194/tc-2019-67
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Past water flow beneath Pine Island and Thwaites glaciers, West Antarctica

Abstract: Abstract. Outburst floods from subglacial lakes beneath the Antarctic Ice Sheet modulate ice flow velocities over periods of months to years. Although subglacial lake drainage events have been observed from satellite altimetric data, little is known about their role in the long term evolution of ice sheet basal hydrology. Here, we systematically map and model past water flow through an extensive area containing over 1000 subglacial channels and 19 former lake basins exposed on over 19,000 km2 of seafloor by th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 74 publications
4
35
0
Order By: Relevance
“…3a). Troughs and channels in the adjacent eastern part of Pine Island Bay have been described comprehensively by Nitsche et al (2013) and Kirkham et al (2019). The larger troughs in our study area, which have also been identified on gravity-derived regional bathymetry maps (Millan et al, 2017;Jordan et al, 2020.…”
Section: Trough and Channel Metricssupporting
confidence: 52%
See 4 more Smart Citations
“…3a). Troughs and channels in the adjacent eastern part of Pine Island Bay have been described comprehensively by Nitsche et al (2013) and Kirkham et al (2019). The larger troughs in our study area, which have also been identified on gravity-derived regional bathymetry maps (Millan et al, 2017;Jordan et al, 2020.…”
Section: Trough and Channel Metricssupporting
confidence: 52%
“…These areas with low surface slopes are atypical when compared with other bathymetric highs in the area, which have rugged surface morphologies characterised by bedrock grooves and channels (Fig. 2, 4d) (Nitsche et al, 2013;Arndt et al, 2018;Kirkham et al, 2019). Instead, the low slope values are similar to those derived for the base of the troughs in front of Thwaites Ice Shelf (Fig.…”
Section: Bathymetric Highs and Ridgesmentioning
confidence: 50%
See 3 more Smart Citations